RANCANG BANGUN SOFTWARE PERHITUNGAN UNTUK SISTEM METER TURBIN DENGAN METODE FUZZY - Astrie Kusuma Dewi; Silvia Mareta; Chalidia Nurin Hamdani (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2022)
Custody transfer is an important activity in the oil and gas industry which requires high accuracy. In keeping the metering system in an accurate condition, dynamic testing is needed as an evaluation of the custody transfer metering system. In carrying out dynamic testing, software is needed so that calculations will be more accurate and minimize errors. Calculation software in the market is currently quite expensive and does not cover all the calculation needs needed in the field, it is necessary to make calculation software that suits your needs and has a low price. With this software, it is hoped that it can simplify the calculation process and speed up troubleshooting time when there is a measurement deviation because the data read in the flowcomp can be directly proven for its accuracy. In finding a correction factor, a method is needed that is able to determine the value between two known values. Fuzzy method is considered capable of solving these problems. Sugeno fuzzy method is suitable for use in this study because it has an output in the form of a constant. After testing several random samples, the results of the Sugeno fuzzy method have the greatest error on the MPMS API table, namely 0.00004. When compared with the interpolation method, the fuzzy method has the same results as the value generated by the interpolation method. So it can be concluded that the fuzzy method can be used as a calculation method in finding the correction factor.